Equity offerings by firms that emerged from bankruptcy - Surendranath Jory; Jeff Madura (The Journal of Entrepreneurial Finance and Business Ventures, 2007)
Entrepreneurship is not only used to create a business idea, but also to restructure a business in response to environmental conditions. Firms that issue equity after emerging from bankruptcy are unique in that they exhibit less asymmetric information than other firms that issue equity. They were previously subject to the SEC disclosure requirements when they had publicly-traded securities, and were required to disclose information about their assets, liabilities, and governance while operating under Chapter 11 bankruptcy laws. Our analysis determines that the mean underpricing of the firms that engaged in public stock offerings after emerging from bankruptcy is 4.49 percent, while the mean underpricing for the traditional IPOs is 15.53 percent. A multivariate analysis reinforces the lower degree of underpricing of public offerings by firms that emerged from bankruptcy, while controlling for other characteristics that could affect the level of underpricing. We also find that the aftermarket stock price performance of the firms that emerged from bankruptcy is more favorable than that of traditional IPOs. All results are attributed to a lower degree of asymmetric information associated with public stock offerings by firms that emerge from bankruptcy.
Keywords: 650